Transnational organized crime and COVID: A book review essay. Issue 1 (March 2023) - Jones, Nathan P
COVID-19, Gangs, and Conflict . Edited by John P. Sullivan and Robert J. Bunker. A Small Wars Journal–El Centro Reader. Bloomington: Xlibris. 2020. Photos. Endnotes. Contributor biographies. Prologue. Foreword. Postscript. Afterword. Selected References. pp. 153. Paperback 12.17. Kindle 3.99. Criminal Contagion: How Mafias, Gangsters and Scammers Profit from a Pandemic . By Tuesday Reitano and Mark Shaw. London: Hurst and Company, 2021. ISBN 9781787384460. Notes. Index. pp. 320. Hardcover 26.95.